Review and evaluation of municipal solid waste management practices in Malaysia - Aja, O.C. (Widener University School of Civil Engineering, 2014)
The review is focused on municipal solid waste (MSW) management practices in Malaysia, waste generation rate, waste composition, and the attitude of the people toward sustainability of waste management practice. Malaysian's MSW management has mainly been landfill where about 80-95 of collected MSW are disposed. Currently, recycling practice is rated at 5 while composting is rarely practiced. Over 30 of collected MSW in Malaysia are recyclable materials but the current status records 5 recovery. Composting has been given poor attention even when over 45 of the MSW generated are organic and biodegradable materials while incineration is still at the early/testing stage. Malaysian MSW is highly commingled because there is no proper sorting thus the waste has high moisture content. Proper sorting at the waste generation point for recovery of reusable materials, recyclable materials and compostable materials will help improve the municipal waste management practice in Malaysia. This will reduce the waste volume sent to landfills and will extend the designed life of the landfills. Awareness on waste reduction is growing but is publicly low implemented which can be attributed to lack of social consciousness.